2019
DOI: 10.1038/s41467-019-10089-0
|View full text |Cite|
|
Sign up to set email alerts
|

Dissociating task acquisition from expression during learning reveals latent knowledge

Abstract: Performance on cognitive tasks during learning is used to measure knowledge, yet it remains controversial since such testing is susceptible to contextual factors. To what extent does performance during learning depend on the testing context, rather than underlying knowledge? We trained mice, rats and ferrets on a range of tasks to examine how testing context impacts the acquisition of knowledge versus its expression. We interleaved reinforced trials with probe trials in which we omitted reinforcement. Across t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…Studies in mice have provided insight into the role and tuning of the auditory cortex and surrounding cortical (Chen et al, 2019) and striatal (Chen et al, 2019;Xiong et al, 2015;Znamenskiy & Zador, 2013) structures, as well as deeper structures such as the basal forebrain (Hangya et al, 2015) and thalamus (Chen et al, 2019). Such research has yielded useful neurobehavioral computational models largely targeted at steady-state behavior (Hangya et al, 2015;Kuchibhotla et al, 2019).…”
Section: Detection Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in mice have provided insight into the role and tuning of the auditory cortex and surrounding cortical (Chen et al, 2019) and striatal (Chen et al, 2019;Xiong et al, 2015;Znamenskiy & Zador, 2013) structures, as well as deeper structures such as the basal forebrain (Hangya et al, 2015) and thalamus (Chen et al, 2019). Such research has yielded useful neurobehavioral computational models largely targeted at steady-state behavior (Hangya et al, 2015;Kuchibhotla et al, 2019).…”
Section: Detection Introductionmentioning
confidence: 99%
“…Additionally, Kurt and Ehret (2010) showed that although amplitude discriminations are more difficult to acquire than frequency discriminations, amplitude discrimination training facilitates acquisition of frequency discriminations. More recently, Kuchibhotla et al (2019) showed that evidence of acquisition appears sooner in a mass of signaled non-reinforced probe trials than in training trials alone, suggesting either that trial spacing affects acquisition expression (Barnes, 1957;Kalmbach et al, 2019;Sunsay et al, 2004) or competition between the reinforcer and task-relevant stimuli for behavioral control interferes with acquisition expression. More recently, while (Xiong et al, 2015) revealed a role for corticostriatal plasticity in acquisition, (Hangya et al, 2015) demonstrated a role for basal forebrain cholinergic neurons projecting to the cortex in signaling and communicating both reward and punishment.…”
Section: Detection Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, learning paradigms in freely moving and behaving animals such as those utilizing touchscreen‐based operant systems simulate more naturalistic foraging behavior with the addition of an appreciable level of experimental control, and while animals have the option to engage in the task (or not), as in the real world. Freely moving and body/head‐fixed behavioral methods may reveal the same underlying process, 1 but there are also important and potentially growing examples of divergence 2,3 …”
mentioning
confidence: 99%